Pseudotomodon Trigonatus (false tomodon snake): Habitat - Pelegrin, Nicolas (2020)
Pseudotomodon trigonatus is a dipsadid snake endemic to Argentina. It is mainly distributed in the Monte Desert ecoregion, but it also occurs in the Mountain Chaco (Giraudo and Scrocchi 2002. Smithsonian Herpetological Information Service 1321–53; Avila 1997. Herpetol. Rev. 28:98). It is generally associated with xerophytic environments in the Monte Desert, and in rocky habitats in the Mountain Chaco...